Community assessment profile and needs of mothers in San Jose City - Gamit, Estrelita T. (2004)
The study was conducted to assess the profile and needs of mothers in Malasin, San Jose City, an Adopt A Barangay Project of the College of Home Science and Industry, Central Luzon State University, Science City of Munoz. The respondents consisted of 133 mothers selected by simple random sampling. Data relevant to the study were collected through survey questionnaire. Results showed that majority of the mothers were young, most of them were high school graduates, their income was much below the poverty threshold. Most of the respondents have one to two siblings and they speak either Tagalog or Ilokano in their homes. Majority of the mothers stayed home and did household chores and they signified their need to learn something about animal production to augment their family income.
Keywords: Mothers